EVALUATION OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE MANAGEMENT PROGRAM IN IMPROVING THE QUALITY OF EDUCATION - ARIFIN, Bustanul (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
Facilities and infrastructure are crucial in supporting the smooth learning process. The teaching and learning process can run effectively with adequate facilities and infrastructure. This study aims to analyze and evaluate the management of educational facilities and infrastructure to improve the quality of education. This research uses a qualitative approach with an evaluation method through the discrepancy model. The study was conducted at SDIT Daar El Khaer, Tigaraksa, Tangerang, involving 5 research subjects: the principal, the head of facilities and infrastructure, the school committee, students, and parents. Data were collected through observation, interviews, and documentation. The results show that the management of facilities and infrastructure complies with regulations and meets students’ needs, although bureaucratic obstacles remain. Facilities and infrastructure that meet government standards account for only 50%-55%. Therefore, schools must focus on managing facilities and infrastructure effectively and streamline bureaucratic processes to meet students' needs according to official standards. This study recommends that the facilities and infrastructure program at SDIT Daar El Khaer be continued while adhering to the latest standards based on Government Regulation No. 57 of 2021 and Minister of Education, Culture, Research, and Technology Regulations No. 22 and 48 of 2023. The implementation must involve all relevant parties, including the school committee. The principal should oversee the implementation of facilities standards by the head of facilities. Schools need to evaluate bureaucratic obstacles, find solutions to improve efficiency, and continuously monitor and enhance their facilities according to regulations to improve educational quality.